Hydration, Hydration, Hydration - Miller, Veronica; Bates, Graham (Oxford University Press, 2010)
Throughout the world, large numbers of manual workers perform physically demanding labour in conditions of high environmental heat stress. Although the importance of adequate hydration in combating heat stress is universally recognized, studies in a range of worker groups have demonstrated a disturbingly poor hydration level in a high proportion of at-risk workers. Management of work in hot environments traditionally focuses on environmental monitoring, while strategies to promote and ensure good hydration behaviour are often haphazard at best. An example is given of simple guidelines for adequate and appropriate fluid intake and practical recommendations to foster compliance.